Badminton Field Booking Application in the Sidoarjo Region based on Android - Rengga Lauddipa; Mohammad Suryawinata (Procedia of Engineering and Life Science, 2021)
In sidoarjo area more and more badminton court rental with quality standards that make fans play badminton more and more. in booking badminton courts still use a manual system. Then it takes innovation in technology to help in booking badminton courts. In the creation of the application using waterfall method so that the creation of the application can be completed according to the planning so as to produce the appropriate application. Implementation of the results of the study using android studio software using java programming language and using firebase database as data storage in the application in realtime. Badminton court booking application based on android can provide user convenience in booking badminton court does not have to come to the field. The application has been tested using the black box testing method on all features of the application shows a percentage of 100% so that arguably the application runs well. Similarly, can be seen in the test using the likert scale questionnaire method for UAT results get a result of 85%.